Epoxidation of Alkenes with Molecular Oxygen Catalyzed by Immobilized Co(acac)2 and Co(bpy)2Cl2 Complexes within Nanoreactors of Al-MCM-41 - F. Farzaneh; M. Jalalian; L. Tayebi (E-Journal of Chemistry)
Cobalt complexes with different ligands such as bipyridine, and acetylacetonate were immobilized within nanoreactors of Al-MCM-41, designated as Co(acac)2/Al-MCM-41 and Co(bipy)22+/Al-MCM41. The immobilized complexes were characterized by XRD, N2-adsorption desorption, FT-IR and UV-Vis techniques. It was found that Co(bipy)22+/Al-MCM41 and Co(acac)2/Al-MCM-41 successfully catalyze the oxidation of norbornene, styrene, cis-stilbene, trans-stilbene, and cyclohexene with 68% to 100% conversion and 41% to 90% selectivity toward the corresponding epoxides. No desorption was observed during the course of reactions.